Survival and reproductive outcome of childbearing age ovarian cancer patients taking fertility-sparing surgery - Yoon, Hye Soo; Chung, Yun Soon; Seo, Jong Wook; Chung, Jae Eun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Surgical management of ovarian cancer includes total hysterectomy and bilateral salpingo-oophorectomy which results in the loss of fertility. Fertility-sparing surgery in the reproductive aged women with early-stage ovarian cancer with favourable histology has been proposed by American College of Obstetrics and Gynecology and European Society for Medical Oncology. We sought to access the survival and fertility outcome of Korean women in their reproductive age who undertook fertility-sparing surgery. Methods: Based on the Korean National Insurance Claims Data and the National Health Information Database, 328 women with newly developed ovarian cancer in 2010 were followed up for the survival and pregnancy outcome until 2020. Patients who were diagnosed with cancer or underwent hysterectomy before 2010 were excluded. The control group consisted of 552 women matched by age, economic status and place of living. Results: Out of 120, 10 deaths occurred in the fertility-sparing surgery group showing a survival rate of 91.7%. Women undertaking fertility-sparing surgery had a lower chance of delivering a new-born compared to the control group (OR 0.46; 95% CI 0.26-0.81). Diagnosis of infertility, ectopic pregnancy, and abortion appeared higher in the fertility-sparing surgery group, but it did not reach a statistical significance. Conclusions: The pregnancy rate of the ovarian cancer patients with fertility-sparing surgery was lower than that of women without ovarian cancer. Undergoing fertility-sparing surgery per se should not deter women of trying to get pregnant as the pregnancy outcome indicators do not show statistically significant differences compared to the control group.